Islamic Republic of Iran - (:unkn) unknown (IGI Global, 2017)
Iran has been a home for prominent civilizations since early ages thanks to its geographical position, at the intersection point of Europe and Asia. Iran also is a very important market for Turkey. Its population is growing adn several ethnical groups takes place in the country. Its economy is growing despite pressure from international society; these restrictions are lifted in the near future. Relations between Iran and Turkey are important for Middle East politics; Ankara and Tehran's lack of cooperation before the issues in the Middle East led the region to further tribulations, resulted in a decrease in their activities not only in the Middle East but also on a global scale. The relations became closer during AK Party governments in Turkey. © 2018, IGI Global. All rights reserved.